Transitions et développement en Afrique :un continent d’incertitude - Géraud Magrin; Olivier Ninot (Bulletin de l’Association de Géographes Français)
Africa provides an interesting case study to reflect on the interest and limits of one of the most common meanings of the polysemic notion of transition (modelling a known trajectory from an initial state to an end state). Indeed, the trajectory of the continent has been thought of since the 1960s through normative perspectives that are framed in terms of transition, as summarized in the Rostowian vision of development. Moreover, in 2020, the continent is engaged in major, multiple transitions (demography, urbanisation, economy, territorial policies), the pace and scale of which are unprecedented. However, these profound changes are in many cases reluctant to fit into established patterns, to the point of questioning the universality of some of them. This contribution finally proposes to discuss the nature of the changes underway, postulating the pre-eminence of uncertainty over the reassuring notion of transition.